2019
DOI: 10.1108/cr-06-2018-0038
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial orientation and performance of small and medium-sized enterprises

Abstract: Purpose This paper aims to investigate the effects of entrepreneurial orientation (EO) on the performance of small and medium-sized enterprises (SMEs) with mediating role of differentiation strategy in Pakistan. Design/methodology/approach A theoretical framework has been developed to base the hypotheses, as also to determine the exact approach in this study. To establish the influence of EO on the performance of SME, a five-point Likert scale questionnaire has been used to collect data from middle and senio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
74
2
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(99 citation statements)
references
References 68 publications
7
74
2
16
Order By: Relevance
“…From Table 4, investment decision making is also positively influenced by overconfidence bias. These results are consistent with the studies conducted by Qadri and Shabbir (2014), Lim (2012), Qureshi et al (2012), Shah et al (2019), and Bashir et al (2013) that report that overconfidence has a significant positive impact on investor's decision making. Meanwhile, the findings are inconsistent with Kafayat (2014), and Kengatharan and Kengatharan (2014) that found that overconfidence does not influence decision making.…”
Section: Regression Resultssupporting
confidence: 92%
“…From Table 4, investment decision making is also positively influenced by overconfidence bias. These results are consistent with the studies conducted by Qadri and Shabbir (2014), Lim (2012), Qureshi et al (2012), Shah et al (2019), and Bashir et al (2013) that report that overconfidence has a significant positive impact on investor's decision making. Meanwhile, the findings are inconsistent with Kafayat (2014), and Kengatharan and Kengatharan (2014) that found that overconfidence does not influence decision making.…”
Section: Regression Resultssupporting
confidence: 92%
“…Majority of the studies conducted on the relationship between entrepreneurial orientation and performance have shown positive impact (Alkhazali et al, 2020). But on the other hand, few researchers contradicted the ndings and highlighted that the relationship between entrepreneurial orientation and performance have insigni cant (Cho & Lee, 2018;Shah & Ahmad, 2019;Hernández-Linares, Kellermanns, López-Fernández, & Sarkar, 2019), or least in uence (Vega-Vázquez, Cossío-Silva, & Revilla-Camacho, 2016; Masa'deh, Al-Henzab, Tarhini, & Obeidat, 2018) or negative (Taheri, Bititci, Gannon, & Cordina, 2019) or curvilinear (Yoon & Solomon, 2017), or inverse U shaped (Luu & Ngo, 2019) relationship. This shows that the ndings cannot be considered as conclusive, which provide justi cation for analysing the construct again.…”
Section: Performance Of Smesmentioning
confidence: 99%
“…Performance of SMEs is a widely researched area. Yet there is no consensus on the way that how the performance should be measured because the major issue with SMEs is informality (Shah & Ahmad, 2019). The nancial records are not properly maintained, and even if the accounts are maintained, they are not audited, therefore, the question of reliability of the accounts can never be resolved.…”
Section: Performance Of Smesmentioning
confidence: 99%
See 2 more Smart Citations